Giving Life Gives Me Life: An Action Research Experience with Families - Eilyn Arce-Chavarría (Universidad Nacional, Costa Rica, 2015)
This paper is the result of a participatory action research project.  It expresses my experiences with nine of the fourteen families of students attending the special education school where I work.  Students are in Early Intervention (0-3 years old), Kinder Garden (3-6 and a half years old) and the first cycle of elementary school (6 years and 6 months to 9 years old). Six of the participating families included a father and a mother, while the other three only included the mother. I met six times with the families for afternoon coffee over the course of a year.  These gatherings evidenced the need for synchronizing the work done at home with the work offered in the occupational therapy service of which I am in charge, in order to support families in developing their children's every day skills.  This involves a process of analysis and reflection, which leads to the transformation of those of us who lived this experience.  The paper also presents the families' reality first from their individual standpoint and later in synchronization with the group, change that was exhibited after sharing with the other families.  Important findings include the need for having a stronger relationship between the school and the families, creating a space for emotional growth for parents, finding similarities between families that would motivate them to be more involved, taking advantage of time, creating personal space for reflection and, last but not least, daring to change.